Influence of soil moisture on the sequestration of organic compounds in soil. - Kottler, Bennett D.; White, Jason C.; Kelsey, Jason W. (Chemosphere, 2001)
A study was conducted as a part of continuing investigation of the effect of soil moisture on the sequestration of organic compounds aged in the soil. Here, experiments focused on the effects of moisture changes within the soil before, during, and after contaminant addition. The extractability of aged (68 d) phenanthrene was greater from soil that had been subjected to wetting and drying cycles prior to solute addition as compared to soil initially maintained at constant moisture. The recovery of phenanthrene added to moist soil was increased relative to extractability from soil that was air-dried at the time of the contaminant addition. Repeated wetting and drying of soil after the addition of atrazine or phenanthrene resulted in decreased extractability of the compounds as compared to samples maintained at constant moisture. A method for rapidly sequestering contaminants is proposed and may be useful in limiting the time required for laboratory studies involving "aged" contaminants. These data build upon the findings of earlier work from our laboratory and indicate that changes in the moisture conditions of soil can affect the availability of sequestered contaminants possibly through alterations in the structure of the natural solid. © 2001 Elsevier Science Ltd.
46 citations (Crossref) [2023-10-31] Citation Key Alias: pop00068 tex.type: [object Object]
Keywords: Aging; Atrazine; Bioavailability; Biological Availability; Extraction; Organic Chemicals; Phenanthrene; Phenanthrenes; Soil; Soil Pollutants; Water; article; atrazine; bioavailability; chemical structure; dept.egm; extraction; leaching; moisture; organic compound; phenanthrene; phenanthrene derivative; soil moisture; soil pollution; solid state; wetting-drying cycle

Citrate-mediated increase in the uptake of weathered 2,2-bis(p-chlorophenyl)1,1-dichloroethylene residues by plants - White, Jason C; Kottler, Bennett D (Environmental Toxicology and Chemistry, 2002)
Experiments were conducted to determine the ability of citrate to enhance the plant uptake of weathered 2,2-bis(p-chlorophenyl)1,1-dichloroethylene (p, p′-DDE) from soil. Plots containing three rows of clover, mustard, hairy vetch, or rye grass were constructed in soils containing p, p′-DDE. On 11 occasions, the rows of each crop received water or sodium citrate (0.005 or 0.05 M). For each crop, there were significant reductions in p, p′-DDE concentration in the soil fractions (near root and rhizosphere) closely associated with the plant versus bulk soil. The roots of each crop accumulated 2 to 5 times more of the weathered contaminant (dry wt) than present in the bulk soil. Citrate (0.05 M) increased the concentration of p, p′-DDE in the roots of clover, mustard, and hairy vetch by 39% compared with vegetation that received water. In batch desorption studies, the release of weathered p, p′-DDE was significantly greater in the presence of 0.05 M citrate than in water. Citrate increased the extracted aqueous concentrations of five metal ions (Al, Fe, Ca, K, Mn) from soil by five- to 23-fold over distilled water. We hypothesize that citrate physically disrupts the soil through chelation of structural metal ions and release of bound humic material, facilitating p, p′-DDE availability and uptake by plants.
53 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/105-453-614-423-729 tex.type: [object Object]
Keywords: 1; 1 dichloro 2; 2 bis(4 chlorophenyl)ethylene; Bioavailability; Biodegradation; Environmental; Brassica; Chelating Agents; Chelation; Citric Acid; Dichlorodiphenyl Dichloroethylene; Drug Interactions; Extraction; Humic Substances; Impurities; Insecticides; Ions; Metals; Organic compounds; Phytoremediation; Plants; Plants (botany); Secale cereale; Sequestration; Soil Pollutants; Soil fractions; Soil pollution; Tissue Distribution; Trifolium; Vegetation; Vicia; Vicia villosa; Water; aluminum; aqueous solution; article; bioavailability; biological uptake; bioremediation; calcium; chelation; citric acid; clover; concentration (parameters); dept.egm; desorption; iron; manganese; metal ion; nonhuman; phytoremediation; plant; plant root; potassium; priority journal; rhizosphere; rye; soil pollution; water